Immunohistochemical Detection of JC Virus in Nontumorous Renal Tissue of a Patient with Renal Cancer but without Progressive Multifocal Leukoencephalopathy - Aoki, Naoto (American Society for Microbiology, 1999)
We performed immunohistochemical staining on the nontumorous renal tissue of 45 patients with renal cancer but without progressive multifocal encephalopathy using JCV-specific antibody. For one patient we found positive staining of the nuclei of the renal collecting ducts. Immunoelectron microscopic examination of the positive cell nuclei revealed electron-dense polyomavirus-like particles.